The Liberal Unionist Party : a History. - Cawood, Ian (International library of political studies., 2012)
The Liberal Unionist party was one of the shortest-lived political parties in British history. It was formed in 1886 by a faction of the Liberal party, led by Lord Hartington, which opposed Irish home rule. In 1895, it entered into a coalition government with the Conservative party and in 1912, it amalgamated with the Conservatives. Ian Cawood here uses previously unpublished archival material to provide the first complete study of the Liberal Unionist party. He argues that the party was a genuinely successful political movement with widespread activist and popular support which resulted in th.